1988
DOI: 10.1111/j.1398-9995.1988.tb00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with partially purified and standardized tree pollen extracts

Abstract: Fifty-four adult patients with tree pollen-induced rhinitis (28), asthma (1), or rhinitis and asthma (25) were selected for immunotherapy with standardized and partly purified tree pollen extracts using a double blind protocol. The selection was based on clinical history, results of nasal or bronchial challenge, skin prick tests and RAST. Further, based on crossed radio-immunoelectrophoresis, sex, age and severity of symptoms, the patients were allocated in matched pairs and the treatment alternatives were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Allergen-specific immunotherapy of Bet v 1-reactive patients with birch pollen extract is indicated according to the guidelines for specific immunotherapy because most birch pollen extracts contain sufficient amounts of Bet v 1 and are mostly standardized regarding their Bet v 1 contents. Since Bet v 1 cross-reacts with the major Fagales pollen allergens and related plant food allergens immunotherapy with birch pollen extract may improve allergy to Fagales pollens and the concomitant oral allergy syndrome [52, 53]. Since Bet v 1 is the most important and abundant allergen in birch pollen and most birch pollen-specific IgE is directed against rBet v 1 [8], it is likely that patients who produce IgE antibodies to birch pollen extract but lack Bet v 1-specific IgE were sensitized against cross-reactive allergens from other sources (e.g.…”
Section: Bet V 1 the Major Birch Pollen Allergen: Predictor For Fagamentioning
confidence: 99%
“…Allergen-specific immunotherapy of Bet v 1-reactive patients with birch pollen extract is indicated according to the guidelines for specific immunotherapy because most birch pollen extracts contain sufficient amounts of Bet v 1 and are mostly standardized regarding their Bet v 1 contents. Since Bet v 1 cross-reacts with the major Fagales pollen allergens and related plant food allergens immunotherapy with birch pollen extract may improve allergy to Fagales pollens and the concomitant oral allergy syndrome [52, 53]. Since Bet v 1 is the most important and abundant allergen in birch pollen and most birch pollen-specific IgE is directed against rBet v 1 [8], it is likely that patients who produce IgE antibodies to birch pollen extract but lack Bet v 1-specific IgE were sensitized against cross-reactive allergens from other sources (e.g.…”
Section: Bet V 1 the Major Birch Pollen Allergen: Predictor For Fagamentioning
confidence: 99%
“…It has been shown that immunotherapy with birch pollen extract and recombinant birch pollen allergen, Bet v 1 and rBet v 1 derivatives induces protective IgG responses against the cross-reactive Fagales pollen and plant food allergens and may improve allergic symptoms to the birch-pollen-related allergen sources [6,7,8, 14,29,30,31]. In particular, injection immunotherapy trials with adjuvant-bound purified recombinant birch pollen allergen Bet v 1 and with genetically modified derivatives of Bet v 1 have demonstrated that treatment with purified Bet v 1 induces highly specific, robust and protective IgG responses not only to natural Bet v 1 [32], but also to Bet v 1-cross-reactive plant allergens [14, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Both forms of therapy were shown to be equally effective in an extensive analysis published in 1988 [6,7,8]. However, a study published 2 years earlier had indicated that a mixture of birch-alder-hazel pollen seemed to be more effective in reducing symptoms than birch pollen extract alone [9].…”
Section: Introductionmentioning
confidence: 99%
“…Second, rBet v 1 was found to inhibit the majority of IgE reactivity to pollen allergens from trees of the order Fagales (alder, hazel, hornbeam) and plant-derived food in patients with birch pollen-related oral allergy syndrome [47, 118]. Third, it has been shown that immunotherapy with birch pollen extract was effective in treating allergies not only to birch, but also to pollens of trees of the Fagales order and to birch-related plant foods [154,155,156,157]. Fourth, it has been demonstrated that patients who reacted exclusively with Bet v 1 had a better clinical outcome when treated with birch pollen extract than patients reacting also with other allergens [158].…”
Section: Rbet V 1 As a Diagnostic Marker Allergen To Identify Genuinementioning
confidence: 99%